MANAJEMEN PEMBELAJARAN EKSTRAKURIKULER DALAM KAITANNYA DENGAN UPAYA MENINGKATKAN PRESTASI SISWA DI SMP NEGERI I PREMBUN KABUPATEN KEBUMEN (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aims at getting and overview of planning, implementing, and accomplishing management of extracurricular instruction in relation to the improvement of students’ achievement in SMP Negeri I Prembun, Kebumen Regency. This study employs qualitative research. The sample of the study was obtained by a purposive sampling technique which was conducted based on various informants of management of extracurricular instruction in relation to the improvement of students’ achievement in SMP Negeri I Prembun, Kebumen Regency. The key informants of this study were The Principal and Teachers. The data collection was obtained by conducting structured and unstructured interview, observation and document review. The data analysis was done by using qualitative data analysis technique, which consist of organizing data trough categorization, grouping, and giving series number based on the chronological order at the time the data were obtained. The data validity was conducted by continuous observation, triangulation of source and method. The result of the study has shown some conclusion namely 1. The arrangement of management of extracurricular instruction in SMP Negeri I Prembun, Kebumen Regency already has been implemented in good way in relation to the improvement of students’ achievement. 2. The achievement of SMP Negeri I Prembun is fairly good; top ten of the biggest score in national examination in Kebumen Regency, and winning at championship events. 3. The implementation of extracurricular instruction has no serious obstacle. 4. The planning, organizing activities, evaluation and supervision of management of extracurricular instruction in SMP Negeri I Prembun has been involving all of school components. The researcher suggests school administrator to continue employing extracurricular instruction to improving students’ achievements since the extracurricular instruction aims to develop and strengthen their talent and preferred learning in line with the field they have decided so the students have good achievement.